2015
DOI: 10.1053/j.semperi.2015.05.009
|View full text |Cite
|
Sign up to set email alerts
|

Pregnancy as a window to future health: Excessive gestational weight gain and obesity

Abstract: Metabolic and behavioral changes that occur during pregnancy have well-known effects on maternal and fetal health during the immediate pregnancy and now are thought to be a catalyst for future health throughout later life. Recommendations for appropriate gestational weight gain (GWG) and lifestyle modifications during pregnancy have changed throughout history as more is known about this crucial time. Herein we discuss the current GWG recommendations and the impact of pregnancy and excess GWG gain on the curren… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
140
1
4

Year Published

2016
2016
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 157 publications
(148 citation statements)
references
References 72 publications
(78 reference statements)
2
140
1
4
Order By: Relevance
“…Other proposed long-term metabolic consequences of excessive GWG for women include type 2 diabetes, cardiovascular disease, and metabolic syndrome. 24 Most importantly, the weight gain that occurs during the first pregnancy, especially if it is excessive and not lost after delivery, is likely to influence future pregnancy outcomes. In this sense, it is important to target nulliparas in our counseling about avoiding excessive GWG.…”
Section: Risks Of Inadequate and Excessive Weight Gainmentioning
confidence: 99%
“…Other proposed long-term metabolic consequences of excessive GWG for women include type 2 diabetes, cardiovascular disease, and metabolic syndrome. 24 Most importantly, the weight gain that occurs during the first pregnancy, especially if it is excessive and not lost after delivery, is likely to influence future pregnancy outcomes. In this sense, it is important to target nulliparas in our counseling about avoiding excessive GWG.…”
Section: Risks Of Inadequate and Excessive Weight Gainmentioning
confidence: 99%
“…23 24 Overweight and excessive gestational weight gain have been linked to development of GDM and later cardiometabolic disorders. 23 [25][26][27] Long-term follow-up studies on development of MeS among women at increased GDM risk are lacking. Our cluster randomised controlled trial (RCT) in Finnish pregnant women at increased GDM risk showed that lifestyle counselling was effective in controlling the proportion of large-for-gestational-age new-borns and improving the women's diet, and preventing excessive gestational weight gain and decrease in physical activity.…”
Section: Introductionmentioning
confidence: 99%
“…Specifically, obese women have higher risk of preeclampsia (Salihu et al 2012), gestational diabetes mellitus (GDM) (Chu et al 2007), and cesarean delivery (Weiss et al 2004), as well as stillbirth and congenital anomalies (Chu et al 2007). In addition, maternal obesity can have a long-term impact on the future health of both the mother and the offspring, especially in terms of heart disease, hypertension, and diabetes (Sridhar et al 2014; Freeman 2010; Gilmore et al 2015). Together with the standard obesity measure of body mass index (BMI), another important measure for maternal obesity is gestational weight gain (GWG) (Ferraro et al 2015).…”
Section: Introductionmentioning
confidence: 99%